Understanding the effects of chitosan, chia mucilage, levan based composite coatings on the shelf life of sweet cherry - TOKSOY ÖNER, EBRU (My University, 2023)
Sweet cherry (Prunus avium L.) fruits are prone to quality and quantity loss in shelf-life conditions and cold storage due to their short post-harvest life. Until now efforts have been made to extend the shelf life of the sweet cherry. However, an efficient and commercially scalable process remains elusive. To contribute to this challenge, here in this study, biobased composite coatings consisting of chitosan, mucilage, and levan, were applied on sweet cherry fruits and tested for postharvest parameters in both market and cold storage conditions. Results demonstrated that the shelf life of sweet cherries can be extended until the 30th day while retaining important post-harvest properties like decreased weight loss, fungal deterioration, increased stem removal force, total flavonoid, L-ascorbic acid, and oxalic acid. Given the cost-effectiveness of the polymers used, the findings of this study indicate the feasibility of extending the shelf-life of sweet cherries on a larger scale.
Keywords: Tarımsal Bilimler; Ziraat; Gıda Mühendisliği; Kimya; Analitik Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Food Engineering; Chemistry; Analytical Chemistry; Natural Sciences; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Temel Bilimler (SCI); Tarım Bilimleri; GIDA BİLİMİ VE TEKNOLOJİSİ; KİMYA, ANALİTİK; Agriculture & Environment Sciences (AGE); Natural Sciences (SCI); AGRICULTURAL SCIENCES; CHEMISTRY; FOOD SCIENCE & TECHNOLOGY; CHEMISTRY, ANALYTICAL; Fizik Bilimleri; Yemek bilimi; Yaşam Bilimleri; Physical Sciences; Food Science; Life Sciences; Cherry; Chitosan; Coating; Levan; Mucilage